PENGARUH STUDENT CENTER LEARNING BERBANTUAN VIDEO YOUTUBE TERHADAP BERPIKIR KRITIS DAN REPRESENTASI MATEMATIS SISWA - Melya Anjly; Bambang Sri Anggoro; Novian Riskiana Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low critical thinking and mathematical representation skills of students are a significant problem in mathematics education, particularly due to the dominance of teacher-centered learning approaches that limit student engagement and understanding of abstract concepts. This study aims to determine the effect of Student Centered Learning (SCL) assisted by YouTube videos on students' critical thinking and mathematical representation skills. This quantitative study used a quasi-experimental design conducted at SMP Negeri 24 Bandar Lampung in grade VIII in the even semester of the 2024/2025 academic year. The research sample consisted of three classes: experimental class 1 which implemented the SCL learning model assisted by YouTube videos, experimental class 2 which used SCL without video assistance, and the control class which used the expository learning model. The data collection instrument was a descriptive test to measure critical thinking and mathematical representation skills that had been tested for validity, reliability, discriminating power, and difficulty level. Data analysis was carried out using the MANOVA test to determine the effect of the learning model on both dependent variables simultaneously. The results of the study showed that there was a significant influence of YouTube video-assisted Student Centered Learning on students' critical thinking and mathematical representation skills. Students who studied with YouTube video-assisted SCL showed higher critical thinking and mathematical representation skills compared to students in the control class. The use of YouTube videos helped students understand abstract mathematical concepts visually, increased their active participation, and strengthened their ability to associate concepts with various forms of mathematical representation. Thus, the application of YouTube video-assisted Student Centered Learning was effective in improving students' critical thinking and mathematical representation skills on the topic of relations and functions.